A Novel Gel Polymer Electrolyte by Thiol-Ene Click Reaction Derived from CO2-Based Polycarbonate for Lithium-Ion Batteries - Wenhan Luo; Kuirong Deng; Shuanjin Wang; Shan Ren; Dongmei Han; Yufei Wang; Min Xiao; Yuezhong Meng (Advances in Polymer Technology)
Here, we describe the synthesis of a CO2-based polycarbonate with pendent alkene groups and its functionalization by grafting methoxypolyethylene glycol in view of its application possibility in gel polymer electrolyte lithium-ion batteries. The gel polymer electrolyte is prepared by an in-situ thiol-ene click reaction between polycarbonate with pendent alkene groups and thiolated methoxypolyethylene glycol in liquid lithium hexafluorophosphate electrolyte and exhibits conductivity as remarkably high as 2.0×10−2 S cm−1 at ambient temperature. To the best of our knowledge, this gel polymer electrolyte possesses the highest conductivity in all relevant literatures. A free-standing composite gel polymer electrolyte membrane is obtained by incorporating the gel polymer electrolyte with electrospun polyvinylidene fluoride as a skeleton. The as-prepared composite membrane is used to assemble a prototype lithium iron phosphate cell and evaluated accordingly. The battery delivers a good reversible charge-discharge capacity close to 140 mAh g-1 at 1 C rate and 25°C with only 0.022% per cycle decay after 200 cycles. This work provides an interesting molecular design for polycarbonate application in gel electrolyte lithium-ion batteries.